A Combined Procedure of Intrastromal Corneal Rings Explantation and Penetrating Keratoplasty in a Patient With Keratoconus: A Case Report - Nuzzi, Raffaele; Tripoli, Flavia; Rossi, Alessandro; Ghilardi, Andrea (Frontiers in Medicine, 2022)
Keratoconus is a progressive, noninflammatory bilateral degeneration of the central and paracentral cornea that can lead to progressive irregular astigmatism. According to the stage of the pathology, different methods of correction can be used: contact lenses, corneal collagen cross-linking (CXL), intrastromal corneal ring segment (ICRS) implantation, and anterior lamellar or penetrating keratoplasty. We evaluated a 31-year-old patient who at the age of 30 was subjected to bilateral ICRS implantation combined with CXL due to keratoconus. This led, after nine months, to ring extrusion in his left eye, corneal thinning and microperforation into the acqueous chamber with residual irregular astigmatism of 4.50 D. cyl.10°. The patient underwent ICRS explantation and PKP during the same surgical session. After 15 months of follow up, the BCVA was 0,2 LogMAR with a residual astigmatism of 6.3 dpt.